Pseudomonas plecoglossicida as a novel bacterium for phosphate solubilizing and indole-3-acetic acid-producing from soybean rhizospheric soils of East Java, Indonesia - Meli Astriani; SITI ZUBAIDAH; ABDUL LATIEF ABADI; ENDANG SUARSINI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Astriani M, Zubaidah S, Abadi AL, Suarsini E. 2020. Pseudomonas plecoglossicida as a novel bacterium for phosphate solubilizing and indole-3-acetic acid-producing from soybean rhizospheric soils of East Java, Indonesia. Biodiversitas 21: 578-586. The use of synthetic fertilizers to grow soybean (Glycine max (L.) Merrill) in a long time, can increase the risk of environmental damage. Therefore, the current study aimed to find phosphate solubilizing bacteria that can produce indole-3-acetic acid (IAA) hormone to minimize the use of chemical fertilizers. Superior isolates selected through characterization of phosphate solubilization activity on Pikovskaya medium, screening of IAA producing bacteria, quantitative estimation of phosphate solubilizing activity using a spectrophotometer, hypersensitivity assay, antagonist within isolate assay, and molecular identification of selected bacterial isolates using 16S rRNA sequencing with primer forward 63f and primer reverse 1387r. Among the isolated bacteria, isolate Arj8 showed the highest phosphate solubilizing activity and IAA production. Molecular identification indicated that isolate Arj8 shared 100% similarity with Pseudomonas plecoglossicida. The highest phosphate solubilizing activity (75.39 mg/L) and IAA production (38.89 ppm) recorded on day-3. Multiple potentialities of P. plecoglossicida as phosphate solubilizing and IAA producing bacterium are a novel finding in the development of bioinoculants as bio-fertilizers that can reduce dependency on synthetic chemical fertilizers.